2010
DOI: 10.1111/j.1471-0528.2010.02801.x
|View full text |Cite
|
Sign up to set email alerts
|

Physical activity and gestational weight gain: a meta-analysis of intervention trials

Abstract: Background High gestational weight gain (GWG) has been found to be associated with a number of adverse perinatal and long-term outcomes.Objectives We aimed to perform a systematic review and metaanalysis to find out whether physical activity in pregnancy might help avoid high GWG.Search strategy A literature search in relevant databases and an additional search by hand through bibliographies of various publications were performed.Selection criteria We included randomised controlled trials on healthy women, wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
164
0
8

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 182 publications
(180 citation statements)
references
References 51 publications
8
164
0
8
Order By: Relevance
“…These reviews were based mainly on observational studies and physical activity levels were usually assessed using a questionnaire. However, a recent meta-analysis of intervention trials found lower mean GWG among the intervention group than the controls (65) . On the whole, it seems that future research may need to use objective measures of physical activity to accurately examine the relationship between physical activity levels and GWG.…”
Section: Discussionmentioning
confidence: 99%
“…These reviews were based mainly on observational studies and physical activity levels were usually assessed using a questionnaire. However, a recent meta-analysis of intervention trials found lower mean GWG among the intervention group than the controls (65) . On the whole, it seems that future research may need to use objective measures of physical activity to accurately examine the relationship between physical activity levels and GWG.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, physical activity during pregnancy was associated with an improved health-related quality of life, lower postpartum Body Mass Index (BMI) and fewer depressive symptoms (Montoya Arizabaleta et al, 2010, Vernon et al, 2010. In a current meta-analysis by Streuling et al (2010) with randomized controlled trials on healthy pregnant women, with increased physical activity as the only intervention, the authors conclude that physical exercise during pregnancy might be successful in restricting gestational weight gain (Streuling et al, 2010).…”
Section: Introductionmentioning
confidence: 96%
“…Interventions based on increasing physical activity (17,18); dietary advice (19); or by a combination of physical activity, supplementary weight monitoring, and nutritional counselling have been shown to be effective in reducing total GWG (20). A recent meta-analyses suggested that dietary measures might be most effective (21).…”
Section: Introductionmentioning
confidence: 99%